Impact of Retail Market Concentration on Differences in Retailers’ Productivity and Business Results - Vukmirović, Goran; Maric, Radenko; Damnjanović, Jelena (Industrija, 2018)
The aim of this paper is to define the degree of the Serbian retail market concentration and to determine the nature of the correlation between market concentration and retailers’ business performances. The main task of the research is to indicate how changes in market share affect the development of the retail sector. Based on financial indicators in retail, realized turnover and profit per employee, the null research hypothesis was tested for proving a significant correlation between the size of market share of retail chains and their productivity and business results. The obtained results show the level of deviation in terms of the differences between the size of market share and productivity and the business result. There is also an obvious increase in the market share of large retail chains which has led to a decrease in the total number of small independent retailers, as well as a rise in market concentration levels. The obtained results, the conducted analyses and tests will point to the potential dangers of the concentration of the national market and define the criteria for achieving a higher degree of homogeneity. Suggestions and guidelines for future research are presented in the paper.
Keywords: Retail chain; Productivity; Market share; Market